Diversidade funcional da metacomunidade de macroinvertebrados aquáticos no nordeste do Brasil - Portela, Marcela Bernardes (2020)
Freshwater ecosystems can have a high diversity of organisms, including aquatic macroinvertebrates. However, anthropogenic activities, such as pollution, silting and predatory fishing, decrease their diversity and alter ecosystem processes. In this context, Conservation Areas (CAs) with full protection, such as National Parks, can contribute to the conservation of aquatic ecosystems, maintaining the diversity of aquatic macroinvertebrates on a regional scale. However, this effectiveness of the role of UCs is still underestimated, as well as the role of the buffer zone (ZA) established in management plans. This thesis aimed to understand the taxonomic and functional composition (food trophic groups and bioindicators) of benthic macroinvertebrates between CA and its ZA, and to verify how the anthropic activity existing in the ZA interferes with benthic invertebrates. In addition, we verified how the hábitat, i.e., dams and streams, interferes with the aquatic macroinvertebrate community. We was carried out this thesis in the Ubajara National Park, Ceará State, Brazil, where it has an extensive network of streams, rivers, weirs and ponds in and around the CA. Collections of aquatic macrointerveins using suber were carried out in aquatic ecosystems of CA and ZA. We identified and screened this material for classification into functional groups. We showed the results that there is a change in the composition of taxa between CA and ZA and in the proportion of detritivores-crushers (higher in CA). Most of the groups with the highest proportion in the CA are intolerant bioindicators, while the largest proportion of individuals in the ZA are bioindicators tolerant to the disturbance. The streams and dams have differences considering the richness of taxa. This work demonstrates that the CAs have an important role in the conservation of aquatic macroinvertebrates, mainly those most sensitive to anthropic disturbance. In addition, the conservation of different types of water bodies in the ZA is important for the greater diversity of aquatic macroinvertebrates.